Expert oracle application express security - Spendolini, Scott (Apress Imprint: Apress, 2013)
Expert Oracle Application Express Security covers all facets of security related to Oracle Application Express (APEX) development.  From basic settings that can enhance security, to preventing SQL Injection and Cross Site Scripting attacks, Expert Oracle Application Express Security shows how to secure your APEX applictions and defend them from intrusion.   Security is a process, not an event.  Expert Oracle Application Express Security is written with that theme in mind. Scott Spendolini, one of the original creators of the product, offers not only examples of security best practices, but also provides step-by-step instructions on how to implement the recommendations presented.  A must-read for even the most experienced APEX developer, Expert Oracle Application Express Security can help your organization ensure their APEX applications are as secure as they can be.